Metabolic Syndrome Calling Models - Abdurashitovich, Zikrillaev Farrux (American Journal of Bioscience and Clinical Integrity, 2024)
Metabolic Syndrome is a collection of metabolic disorders that increase the risk of cardiovascular diseases, diabetes, stroke, and other health issues. These disorders include central obesity, hypertension, insulin resistance, and atherogenic dyslipidemia. In many countries, approximately 20-30% of the adult population suffers from MetS, and its prevalence depends on factors such as age, gender, ethnicity, and diagnostic criteria. By 2035, the prevalence of MetS is expected to increase to around 53% . This combination of metabolic disorders was first discussed by Dr. Reaven in 1988. At that time, this clinical condition was referred to by various names, such as "insulin resistance syndrome," "syndrome X," and "the deadly quartet" with hypertriglyceridemia. However, it is now most commonly known as metabolic syndrome and is increasingly recognized as a major cardiovascular risk factor.